Common variants in SATB2 are associated with schizophrenia in Uygur Chinese population. (August 2019) - Zhou, Juan; Chen, Jianhua; Xu, Wei; Liu, Yahui; Song, Zhijian; Wen, Zujia; Jian, Xuemin; Yu, Jiezhong; Ma, Xiaojun; Wang, Zhuo; Pan, Dun; Yi, Qizhong; et al.
Abstract : Objective: Schizophrenia is one of the most severe mental disorders and its etiology is supposed to be an interaction between genes and environmental factors. Previous genome-wide association studies of schizophrenia have reported multiple susceptibility loci including rs6704641 in the SATB2 gene. Recently, this locus was further confirmed as a genome-wide significant locus for association with schizophrenia by trans-ancestry meta-analysis of Han Chinese and Caucasian samples. However, there is no report of genetic analysis in Uygur Chinese population, which is considered to have a combined genetic background between eastern Asia and Caucasian. This study is aimed to explore whether SATB2 gene is significantly associated with schizophrenia in Uygur Chinese population, thus providing additional evidence for elucidating the role of SATB2 gene in schizophrenia. Participants and methods: In this study, we performed a case–control analysis focusing on seven tag single nucleotide polymorphisms located in SATB2 gene among 985 patients with schizophrenia and 1218 healthy controls recruited from the Xinjiang Province of China. Results: We found that rs6704641 was significantly associated with schizophrenia in both allelic and genotypic distributions ( P allele = 0.008, P genotype = 0.028 after correction). In addition, rs16831466 is significantly associated with schizophrenia in allelic distributions (corrected P allele = 0.041). Besides, several haplotypes of single nucleotide polymorphism are significantly associated with schizophrenia too. Conclusion: Our results suggest that SATB2 is also a susceptibility gene for schizophrenia in Uygur Chinese population, and subsequent functional experiments are necessary to reveal its role in the pathogenesis. Abstract : Supplemental Digital Content is available in the text.